Habitus camponês-caboclo, prática social camelô: duração e adaptação de processos intersubjetivos sobre o mundo do trabalho na Amazônia - LINS, Alexandre Sócrates Araujo de Almeida (Universidade Federal do Pará, 2019)
This study aims to discuss the long duration of informality in the Amazonian economy from a cultural perspective. The high rates of this phenomenon in Pará (above the national average) point that it can not be studied in the light of a conception that summarizes the economy to the market. In this sense, a qualitative research was conducted, with orientation in the human and social sciences to demonstrate how some cultural dispositions persist through time, while also negotiating with the dynamics of contemporary capitalism. The hypothesis is that these urban workers share the same habitus of what Costa (1994, 2009a, 2009b, 2009c, 2012a, 2012b) called a peasant-caboclo, and that this may be the key to understanding your professional dispositions, especially the temporal ones. It was therefore tried to demonstrate that the work of the street vendor re-enacts in the urban environment what Bourdieu (2009) calls habitus, as a system of durable dispositions and incorporated pre-reflexively. For this work, the most important aspect of the peasant-caboclo habitus shared by today's street workers is a kind of spirit of autonomy that has defied the ruling classes for centuries. These rural workers have historically used their labor force for their own benefit, thus availing of surplus resources that could not be appropriated, at least significantly, by an elite or the state. It was the challenging conditions of the Amazonian rainforest that, for so long, created and maintained this habitus, which even in a position of subalternity, could be imposed in the world of work, even in a dominated position, through a knowledge that coincides with the domain of the environment. In order to understand the extent to which these sediments of the peasant-caboclo are or are not in the camelot, this research carried out 10 interviews in the commercial center of Belém, where the camelô work was approached as a total social phenomenon, according to Mauss's (2003) model. It was reported that street vendors embody contradictory practices. They are revolutionaries as to the forms of use of the public space, and in the desire of "control" of the time and the surplus that they create with the own work, but conservative in the customs. The logic of family reproduction prevails among them, without ceasing to possess an economic rationality that establishes a calculation between time spent and resources earned